Role of conventional immunomarkers, HNF4-α and SATB2, in the differential diagnosis of pulmonary and colorectal adenocarcinomas - Kriegsmann, Mark; Harms, Alexander; Longuespée, Rémi; Muley, Thomas; Winter, Hauke; Kriegsmann, Katharina; Kazdal, Daniel; Goeppert, Benjamin; Pathil-Warth, Anita; Warth, Arne (Histopathology, 2018)
Aims: Pulmonary (ADC) and colorectal (CRC) adenocarcinomas are frequent entities in pathological routine diagnostics. Whereas the differential diagnosis is usually straightforward based on histomorphology, it can be challenging in small biopsies. In general, CDX-2, CK20, Napsin-A and TTF-1 are recommended immunohistological markers in this scenario. Hepatocyte nuclear factor 4 alpha (HNF4-α) and special AT-rich sequence-binding protein 2 (SATB2) were described recently as promising additional markers, but comprehensive large-scale data are lacking so far. Therefore, we analysed the expression of these six markers in 1021 non-small-cell lung cancers (NSCLC), including 472 ADC as well as in 80 pulmonary metastases of CRC. Methods and results: Tissue microarrays of NSCLC and pulmonary metastases of CRC were stained for CDX-2, CK20, HNF4-α, Napsin-A, SATB2 and TTF-1 and staining results were correlated with clinicopathological variables. ADC exhibited expression of CDX-2, CK20, HNF4-α, Napsin-A, SATB2 and TTF-1 in nine (2%), 21 (4%), 17 (4%), 345 (73%), 35 (7%) and 408 (86%) samples, while 80 CRC were positive in 79 (99%), 74 (93%), 77 (96%), no (0%), 78 (98%) and five (6%) cases, respectively. Conclusions: In addition to conventional immunomarkers, HNF4-α and particularly SATB2 may be helpful in the differential diagnosis of pulmonary ADC and metastases of CRC.